Role of gamma knife radiosurgery in the treatment of prolactinomas - Ježková, Jana; Hána, Václav; Kosák, Mikuláš; Kršek, Michal; Liščák, Roman; Vymazal, Josef; Pecen, Ladislav; Marek, Josef (Pituitary, 2019)
PURPOSE: Stereotactic radiosurgery is one of the treatment options for prolactinomas, the most commonly used being Gamma Knife Radiosurgery (GKRS). GKRS is indicated mainly in the treatment of dopamine agonist (DA)-resistant prolactinomas. In our study, we report on our experience in treating prolactinoma patients by GKRS. METHODS: Twenty-eight patients were followed-up after GKRS for 26-195 months (median 140 months). Prior to GKRS, patients were treated with DAs and 9 of them (32.1%) underwent previous neurosurgery. Cavernous sinus invasion was present in 16 (57.1%) patients. Indications for GKRS were (i) resistance to DA treatment (17 patients), (ii) drug intolerance (5 patients), or (iii) attempts to reduce the dosage and/or shorten the length of DA treatment (6 patients). RESULTS: After GKRS, normoprolactinaemia was achieved in 82.1% of patients, out of which hormonal remission (normoprolactinaemia after discontinuation of DAs) was achieved in 13 (46.4%), and hormonal control (normoprolactinaemia while taking DAs) in 10 (35.7%) patients. GKRS arrested adenoma growth or decreased adenoma size in all cases. Two patients (8.3%) developed hypopituitarism after GKRS. Prolactinoma cystic transformation with expansive behaviour, manifested by bilateral hemianopsia, was observed in one patient. CONCLUSIONS: GKRS represents an effective treatment option, particularly for DA-resistant prolactinomas. Normoprolactinaemia was achieved in the majority of patients, either after discontinuation of, or while continuing to take, DAs. Tumour growth was arrested in all cases. The risk of the development of hypopituitarism can be limited if the safe dose to the pituitary and infundibulum is maintained.
Keywords: Hemianopsia; Dopamine Agonists; Hypopituitarism; výsledek terapie; Prolactinoma; hypopituitarismus; Middle Aged; mužské pohlaví; Adult; hemianopsie; mladý dospělý; Radiosurgery; Young Adult; ženské pohlaví; prolaktinom; Humans; lidé středního věku; agonisté dopaminu; dospělí; Female; Treatment Outcome; radiochirurgie; lidé; Male